Comparison of provider-documented and patient-reported brief intervention for unhealthy alcohol use in VA outpatients. (1st August 2015) - Lapham, Gwen T.; Rubinsky, Anna D.; Shortreed, Susan M.; Hawkins, Eric J.; Richards, Julie; Williams, Emily C.; Berger, Douglas; Chavez, Laura J.; Kivlahan, Daniel R.; Bradley, Katharine A.
Highlights: We examined the association between provider EMR-documented and patient-reported brief intervention (BI). We evaluated whether the association varied across 21 US Veterans Affairs networks. There was high agreement between documented BI and patient-report of BI. However, there was no variation in this relationship across VA networks. Provider EMR-documentation of BI may be a valid method for assessing BI quality. Abstract: Background: Performance measures for brief alcohol interventions (BIs) are currently based on provider documentation of BI. However, provider documentation may not be a reliable measure of whether or not patients are offered clinically meaningful BIs. In particular, BI documented with clinical decision support in an electronic medical record (EMR) could appear identical irrespective of the quality of BI provided. We hypothesized that differences in how BI was implemented across health systems could lead to differences in the proportion of documented BI recalled and reported by patients across health systems. Methods: Male outpatients with unhealthy alcohol use identified by confidential satisfaction surveys (2009–2012) were assessed for whether they reported receiving BI in the past year (patient-reported BI) and whether they had BI documented in the EMR during the same period (documented BI). We evaluated and compared the prevalence of documented BI to patient-reported BI across 21 VA networks to determine whether documented BI had a variable association with patient-reported BI across the networks. Results: Of 9896 eligible male outpatients with unhealthy alcohol use, 59.0% (95% CI 57.4–60.5%) reported BI (50.4–64.9% across networks) and 37.4% (95% CI 36.0–38.9%) had BI documented in the EMR (28.0–44.2% across networks). Overall, 72.9% (95% CI 70.8–75.5%) of patients with documented BI also reported BI. The association between documented BI and patient-reported BI did not vary across VA networks in adjusted logistic regression models. Conclusions: Performance measures of BI that rely on provider documentation in EMRs appear comparable to patient report for comparing care across VA networks.